PENGARUH KOMPENSASI DAN BEBAN KERJA TERHADAP TURNOVER INTENTION MELALUI KEPUASAN KERJA KARYAWAN PT GANDAERAH HENDANA KECAMATAN UKUI KABUPATEN PELALAWAN - Arubia, Alung Mela; Marzolina, Marzolina; Fitri, Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this study was to determine the effect of compensation, workload on turnover intention through job satisfaction at PT Gandaerah Hendana. The sample in the study was carried out by means of a census, namely making the entire population a sample of 60 employees. Primary data was collected using a questionnaire as an instrument to prove research results, to test hypotheses. In this study using the help of the SmartPLS 3.0 program. The results of the study show that: 1) The compensation variable has a direct, positive/unidirectional and significant effect on turnover intention, 2) The compensation has a direct, positive/unidirectional and significant effect on job satisfaction, 3) The job satisfaction has a direct, negative and significant effect on turnover intention, 4) Workload has direct effect on turnover intention positively/unidirectionally and significantly 5) Workload has direct effect on job satisfaction positively/unidirectionally and significantly 6) The role of job satisfaction as a mediating of compensation on turnover intention is partial (partial mediation), 7) The role of job satisfaction as a mediating of workload on turnover intention is perfect (complete mediation). Keywords: Compensation, Workload, Turnover Intention, Job Satisfaction